Improving the accuracy of determining the character saturation reservoirs on the results of log interpretation in the oil field "K"(Tomsk region) - Rogov, Aleksey Aleksandrovich (IOP Publishing, 2015)
Log interpretation has revealed a number of factors that have a significant impact on the determination of reservoir fluid content (oil saturation factor). The presented research paper is focused on the analysis of petrophysical properties of reservoir fluids considering laboratory studies of core samples. Based on core sample analysis, data of laboratory studies have been correlated to estimates of radioactive logging and high-frequency induction logging. To determine the oil saturation factor a method which considers the effect of mixed clay on reservoir fluid saturation has been proposed.
Keywords: резервуары; нефтяные месторождения; нефтенасыщенность; петрофизические свойства; пластовые флюиды; каротаж